Antibody status following booster vaccination against SARS‐CoV‐2 virus in patients with haematologic malignancies. (7th November 2022) - Ikeda, Daisuke; Terao, Toshiki; Fukumoto, Ami; Uesugi, Yuka; Tabata, Rikako; Kuzume, Ayumi; Tsushima, Takafumi; Miura, Daisuke; Narita, Kentaro; Takeuchi, Masami; Yamashita, Takeshi; Takamatsu, Hiroyuki; et al.
Summary: Antibody titres in 462 patients with haematological malignancies after the second (D2) and third (D3) SARS‐CoV‐2 vaccine were compared with those of healthy controls (HCs). Significant decay of antibody titre was observed pre D3, but titre surged post D3. The number of seronegative patients decreased from 79 (17.1%) to 44 (9.5%) from post D2 to post D3, and patients with adequate antibody titre increased from 204 (44.2%) to 358 (77.5%). Of the patients who received B‐cell‐targeted therapy, 80% were seronegative and 71% remained seronegative after D3. CD19+, CD4+, CD8+ cell counts, and immunoglobulin G (IgG) levels were identified as independent predictors for adequate serologic response.